Hambatan Guru Matematika Dalam Mengimplementasikan Kurikulum Merdeka Di Sekolah Dasar - Novi Andri Nurcahyono; Jaya Dwi Putra (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The purpose of this research is to identified and described the obstacles for teachers to implement an merdeka curriculum in mathematics learning. The method used in this study is a qualitative descriptive method through interviews and observations to 27 participants of mathematics teachers primary school in West Java. The results of this study indicated that teachers experience obstacles in implementing the merdeka Curriculum in learning Mathematics. Obstacles experienced by teachers in planning, implementing, and evaluating learning. Obstacles to learning planning include (1) lack of understanding of how to reduce/translate CP into learning objectives; (2) heterogeneity of students in the classroom; (3) lack of reference for differentiated learning models; (4) limited facilities and infrastructure in schools; (5) limited initial knowledge and subject matter. Obstacles to the implementation of learning include (1) limited understanding of the subject matter with other relevant knowledge; (2) limitation of accommodating opening questions; (3) the limitations of students' psychological understanding; (4) the limitations of translating knowledge into easily understood language. Obstacles to learning evaluation include (1) an inappropriate preliminary assessment paradigm; (2) the limitations of identifying the learning process; (3) limited understanding of formative assessment.